2021
DOI: 10.1186/s12920-021-01063-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an expanded targeted sequencing panel for non-invasive prenatal diagnosis of sporadic skeletal dysplasia

Abstract: Background Skeletal dysplasia (SD) is one of the most common inherited neonatal disorders worldwide, where the recurrent pathogenic mutations in the FGFR2, FGFR3, COL1A1, COL1A2 and COL2A1 genes are frequently reported in both non-lethal and lethal SD. The traditional prenatal diagnosis of SD using ultrasonography suffers from lower accuracy and performed at latter gestational stage. Therefore, it remains in desperate need of precise and accurate prenatal diagnosis of SD in early pregnancy. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…We can see that most of them were published in 2021 (13 out of 51 studies), likely due to the relatively young age of the investigation technique. Regarding the reviewed studies, 13 are described in the first section concerning the role of cffDNA in the non-invasive prenatal diagnosis of aneuploidies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], 7 are described in the second section (CNV diseases) and the remaining 31 are in the third section concerning diseases with monogenic transmission [ 2 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can see that most of them were published in 2021 (13 out of 51 studies), likely due to the relatively young age of the investigation technique. Regarding the reviewed studies, 13 are described in the first section concerning the role of cffDNA in the non-invasive prenatal diagnosis of aneuploidies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], 7 are described in the second section (CNV diseases) and the remaining 31 are in the third section concerning diseases with monogenic transmission [ 2 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in these diseases the ultrasonographic diagnosis is often inaccurate and late. In all the cited sources [ 21 , 26 , 34 ] a correct identification of the mutation in affected subjects has been reported. In particular, the study by Yin et al [ 26 ] assessed the fetal genotype of any locus using maternal plasma, through a novel genotyping algorithm named pseudo tetraploid genotyping (PTG).…”
Section: Resultsmentioning
confidence: 99%
“…Most noninvasive exclusion of paternal variant reports published to date rely on massively parallel sequencing (MPS) (as recently published for skeletal dysplasia [22]). With an experimental workflow of a few hours, noninvasive prenatal diagnosis by paternal variant exclusion with droplet digital PCR appears to be a valuable option considering MPS costs and turnaround time, as sample processing and sequencing take several days.…”
Section: Discussionmentioning
confidence: 99%
“…Many high-throughput sequencers are compatible with targeted genome sequencing, and have been widely applied in scienti c studies and clinical diagnosis. NextSeq550 system (Illumina), a exible sequencing platform with multiple read length and output con gurations, has been commonly used in WES, transcriptome, as well as targeted sequencing 8,9 . It was reported that the TSO500 panel performed well for variant screening of myeloid neoplasm coupled with the NextSeq550 platform 10 .…”
Section: Introductionmentioning
confidence: 99%